Media regulation, public interest and the law - Whitehouse, Mike, 1961- (Edinburgh University Press, 1999)
"The commercialisation and privatisation of the communication industries poses a fundamental threat to democratic values, and this book argues that regulators will only successfully protect such values if 'citizenship' is recognised as the rationale and objective for the regulatory endeavour. Uniquely, the book considers fully the actual and potential utility of legal mechanisms in the design and implementation of regulatory institutions."--Jacket.